2016
DOI: 10.1002/ana.24572
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance imaging spectrum of succinate dehydrogenase–related infantile leukoencephalopathy

Abstract: Background Succinate dehydrogenase-deficient leukoencephalopathy is a complex II-related mitochondrial disorder for which the clinical phenotype, neuroimaging pattern and genetic findings have not been comprehensively reviewed. Methods 19 individuals with succinate dehydrogenase deficiency-related leukoencephalopathy were reviewed for neuroradiologic, clinical and genetic findings as part of Institutional Review Board approved studies at Children's National Health System (Washington, DC) and VU University Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…Information on genetic testing of other family members was not available. Both mutations have been reported previously; c.143A>T (p.Asp48Val) has been found homozygous and compound heterozygous in patients with leukodystrophy and complex II deficiency (Alston et al 2012;Helman et al 2015), whereas the c.689G>A (p.Arg230His) mutation has been reported in heterozygous form in two patients with apparently sporadic paraganglioma/pheochromocytoma (Amar et al 2005), in a family with paraganglioma/ pheochromocytoma and renal cell cancer (Ricketts et al 2012), as well as in patients with head and neck paraganglioma (Cerecer-Gil et al 2010;Peterson et al 2014). …”
Section: Patientmentioning
confidence: 71%
See 4 more Smart Citations
“…Information on genetic testing of other family members was not available. Both mutations have been reported previously; c.143A>T (p.Asp48Val) has been found homozygous and compound heterozygous in patients with leukodystrophy and complex II deficiency (Alston et al 2012;Helman et al 2015), whereas the c.689G>A (p.Arg230His) mutation has been reported in heterozygous form in two patients with apparently sporadic paraganglioma/pheochromocytoma (Amar et al 2005), in a family with paraganglioma/ pheochromocytoma and renal cell cancer (Ricketts et al 2012), as well as in patients with head and neck paraganglioma (Cerecer-Gil et al 2010;Peterson et al 2014). …”
Section: Patientmentioning
confidence: 71%
“…While heterozygous SDHB mutations are a well-known cause of familial paraganglioma/pheochromocytoma (Ricketts et al 2010), bi-allelic mutations in SDHB have been identified in only a few patients with complex II deficiency and a progressive neurological phenotype with onset in infancy (Alston et al 2012;Helman et al 2015). Here, we present two further patients with bi-allelic SDHB mutations causing complex II deficiency and a progressive neurological disease with leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations